Familial dietary intervention in children with excess body weight and its impact on eating habits, anthropometric and biochemical parameters - Strączek, Kamilla; Horodnicka-Józwa, Anita; Szmit-Domagalska, Justyna; Jackowski, Tomasz; Safranow, Krzysztof; Petriczko, Elżbieta; Walczak, Mieczysław (Frontiers in Endocrinology, 2022)
Introduction: Obesity is considered a civilisation disease which increases mortality and impairs quality of life, also among children and adolescents. Poor eating habits and lack of exercise, as well as incorrect family dietary patterns are considered common causes of increased prevalence of obesity. Dietary education programmes are one of the ways to improve the health status of children and adolescents with overweight and obesity. To be fully effective, these programmes should involve the whole family. Aim of the study: In the face of constantly increasing prevalence of overweight and obesity in the developmental age population and the lack of effective methods to combat its occurrence, it seems appropriate to try to assess the effectiveness of a one-year-long dietary education of children and adolescents with excess body weight on their eating habits and the eating habits of their mothers, as well as selected anthropometric and biochemical parameters in these children using a simple educational tool, the Healthy Food Pyramid. Patients and Methods: The study group consisted of 68 children with overweight and obesity, patients of our Clinic. The study used a proprietary questionnaire to assess dietary habits. Patients and their mothers participated in six individual educational meetings over a twelve-month period. Eating habits were assessed in children and mothers before and after dietary intervention. Sixty-seven questionnaires filled by the mothers and sixty-eight questionnaires filled by children were used for analysis. Results: Sixty-eight children completed the study (72.3%). Those who did not complete the study came from families living in rural areas and their mothers mostly had primary or vocational education. One-year dietary education resulted in significant reduction of BMI SDS by 0.8, waist circumference SDS by 0.77, WHtR by 0.04, and reduction of adipose tissue by 1.76 kg as well as increase in lean muscle weight by 1.34 kg. Moreover, a reduction of LDL-Ch by 6.29 mg/dl, TG by 16.95 mg/dl and increase of HDL-Ch by 5.31 mg/dl was achieved. The one-year dietary intervention did not have the same effect on the change in dietary habits in children and in their mothers.